Double-layer arch structure reinforced mechanoluminescence response composite material and preparation method thereof
The mechanoluminescent material with a double-layer arched structure and porous design solves the problem of sluggish response of ZnS:Cu material to normal force, and achieves efficient force-light conversion and strong luminescence response, making it suitable for complex stress environments.
Patent Information
- Application Number
- CN202511033171.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-11-07
AI Technical Summary
Existing ZnS:Cu mechanoluminescent materials are sluggish in response to normal forces, which limits their application in complex stress environments, and traditional materials are insufficient in force-to-light conversion efficiency.
The design employs a double-layer arched structure combined with a porous structure. Through a geometric mechanical conversion mechanism, normal pressure is efficiently converted into multi-directional tangential force coupling. The porous structure is also introduced to optimize the force-light conversion efficiency and improve the ZnS:Cu luminescent material's ability to sense normal force.
It significantly improves the ability of ZnS:Cu luminescent materials to sense normal forces, enhances the intensity and efficiency of mechanoluminescence response, and is suitable for application in complex stress environments.
Smart Images

Figure CN120904885A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of mechanoluminescence materials and devices, and particularly relates to a composite material with a double-layer arched structure for enhancing mechanoluminescence response and a preparation method thereof. BACKGROUND
[0002] Mechanoluminescence (ML) is a luminescence phenomenon under mechanical stimulation such as stretching, rubbing and grinding. In recent years, ML has attracted attention of researchers due to its potential applications in pressure sensing, display, biological imaging and research on luminescence principles. Among them, ML materials and ML sensors are a technical field with great application value and research prospect.
[0003] With the deepening of the research on ML sensors, although the current ML sensors have shown good performance in some application scenarios, the traditional ML materials such as ZnS:Cu still face many technical challenges. In particular, the ZnS:Cu material is sensitive to tangential force but dull to normal force, which limits its application in complex stress environments.
[0004] Therefore, it is necessary to research and improve the ZnS:Cu material, improve its response sensitivity to complex stress, and optimize its force-light conversion efficiency. SUMMARY
[0005] The present application aims to at least solve one of the technical problems existing in the prior art. To this end, the present application provides a composite material with a double-layer arched structure for enhancing mechanoluminescence response and a preparation method thereof. The mechanoluminescence material for enhancing mechanoluminescence response of the present application efficiently converts normal pressure into multi-directional tangential force coupling through a geometric mechanics conversion mechanism, and introduces a porous structure design to further optimize the force-light conversion efficiency, thereby significantly improving the perception ability of the ZnS:Cu luminescent material to normal force.
[0006] The present application also provides a preparation method of the above-mentioned mechanoluminescence material for enhancing mechanoluminescence response.
[0007] The present application also proposes an application of the mechanoluminescence material for enhancing mechanoluminescence response.
[0008] In a first aspect of the present application, a composite material with a double-layer arched structure for enhancing mechanoluminescence response is provided, and the composite material is a double-layer arched structure composed of a support layer and a luminescent layer; the preparation raw materials of the support layer include PDMS, a curing agent and SiO2; and the preparation raw materials of the luminescent layer include PDMS, a curing agent and a ZnS:Cu mechanoluminescence material.
[0009] According to the specific embodiments of the present application, the force-induced light-emitting composite material of the arch structure can overcome the limitations of ZnS:Cu luminescent material in normal force sensing, and efficiently convert normal pressure into multi-directional tangential force coupling through a geometric mechanics conversion mechanism; when the normal load acts on the arch top, the arch curved surface generates a non-uniform strain distribution: the top region forms a compressive stress, and the arch foot region generates a tensile stress and a shear stress, and through this conversion mechanism, the sensing ability of the ZnS:Cu luminescent material to the normal force is significantly improved.
[0010] According to some embodiments of the present application, the composite is a porous arch structure, and the porous structure exists in the light-emitting layer.
[0011] According to the specific embodiments of the present application, the present application introduces a porous structure design into the arch structure to obtain a porous arch structure force-induced light-emitting material, and further optimizes the force-light conversion efficiency; the porous arch structure force-induced light-emitting material of the present application realizes performance breakthrough through multi-stage deformation coupling and light field modulation; the porous structure forms local stress concentration at the hole edge, so that the local strain of the ZnS:Cu particles is improved; at the same time, the secondary shear slip is generated by the hole wall buckling, and the additional triboelectric effect is excited; in addition, the porous structure reduces the average refractive index of the material and reduces the total internal reflection loss, and can significantly improve the intensity of the ML.
[0012] According to some embodiments of the present application, in the preparation raw materials of the support layer, the mass ratio of PDMS, curing agent and SiO2 is in the range of 10:(0.5-2):(0.4-1).
[0013] According to some embodiments of the present application, in the preparation raw materials of the support layer, the mass ratio of PDMS, curing agent and SiO2 is in the range of 10:(0.8-1.5):(0.5-0.8).
[0014] According to some embodiments of the present application, in the preparation raw materials of the support layer, the mass ratio of PDMS, curing agent and SiO2 is in the range of 10:(0.8-1.2):(0.5-0.7).
[0015] The present application explores and finds that when a suitable mass fraction of SiO2 is added to the PDMS base material, the support layer material exhibits optimal comprehensive toughness characteristics, has a high elastic modulus and good ductility, and is suitable for being used as a support layer to generate sufficient recovery stress in the bending release process.
[0016] According to some embodiments of the present application, in the preparation raw materials of the light-emitting layer, the mass ratio of PDMS, curing agent and ZnS:Cu force-induced light-emitting material is in the range of 10:(0.5-2):(5-15).
[0017] According to some embodiments of the present application, the mass ratio of PDMS, curing agent and ZnS:Cu mechanoluminescent material in the preparation raw material of the light-emitting layer ranges from 10:(0.8-1.5):(8-12).
[0018] According to some embodiments of the present application, the mass ratio of PDMS, curing agent and ZnS:Cu mechanoluminescent material in the preparation raw material of the light-emitting layer ranges from 10:(0.8-1.2):(8-12).
[0019] According to some embodiments of the present application, the curing agent is a commonly used curing agent for PDMS well known in the art.
[0020] According to some embodiments of the present application, the curing agent is the curing agent in Dow Corning SYLGARD 184 silicone rubber product.
[0021] According to some embodiments of the present application, the preparation raw material of the light-emitting layer further comprises water-soluble particles, the particle size of the water-soluble particles ranges from 50 to 500 μm; and the mass ratio of the PDMS to the water-soluble particles ranges from 10:(10-30).
[0022] According to some embodiments of the present application, the water-soluble particles are water-soluble metal salt particles.
[0023] According to some embodiments of the present application, the water-soluble particles are metal salt particles of NaCl, KCl, CaCl2, MgCl2 and the like which are easily soluble in water.
[0024] According to some embodiments of the present application, the particle size of the water-soluble particles ranges from 50 to 400 μm, which can be optionally 100-400 μm, 50-300 μm, 50-200 μm and the like.
[0025] According to some embodiments of the present application, the mass ratio of the PDMS to the water-soluble particles ranges from 10:(15-25).
[0026] According to some embodiments of the present application, the mass ratio of the PDMS to the water-soluble particles ranges from 10:(18-22).
[0027] According to some embodiments of the present application, the thickness of the support layer is 100-200 μm, and the thickness of the light-emitting layer is 300-600 μm.
[0028] According to some embodiments of the present application, the thickness of the support layer is 120-160 μm, and the thickness of the light-emitting layer is 400-500 μm.
[0029] The optimization of the thickness range of the support layer and the light-emitting layer and the thickness ratio range of the two, a thicker light-emitting layer is equivalent to increasing the arm length of the "lever", when the light-emitting layer coating is thickened, the neutral axis will be upwardly deviated, so that the force arm of the high modulus layer contraction force is significantly increased, although the overall structure is thickened, the bending stiffness is slightly increased, but the bending moment (proportional to the first power of thickness) increases far more than the stiffness (related to the third power of thickness), and finally the curvature is increased, so that it is easier to form an arch, thereby enhancing the geometric mechanics conversion mechanism of the force-induced light-emitting material of the present application, and further improving the perception ability to the normal force.
[0030] In a second aspect, the present application provides a preparation method of the composite material with a double-layer arch structure for enhancing the force-induced light-emitting response, comprising the following steps:
[0031] S1, mixing the preparation raw materials of the support layer, coating on the substrate, drying and curing to form the support layer, and applying a horizontal tensile force to the support layer, stretching to 105% to 140% of the original horizontal length;
[0032] S2, mixing the preparation raw materials of the light-emitting layer, coating on the support layer in the stretched state, drying and curing to form the light-emitting layer, and releasing the tensile force of the support layer to form a composite material with a double-layer arch structure.
[0033] According to some embodiments of the present application, when the preparation raw materials of the light-emitting layer include water-soluble particles, the following steps are further included:
[0034] The composite material obtained in step S2 is placed in hot water and ultrasonically treated to dissolve the water-soluble particles, thereby obtaining a composite material with a porous arch structure.
[0035] According to some embodiments of the present application, the drying and curing method in steps S1 and S2 is heating and curing at 70 to 90°C for 1 to 3 hours.
[0036] According to some embodiments of the present application, the coating method in steps S1 and S2 is using a spin coater to spin coat at a speed of 200 to 1500 rpm / min for 30 to 90 seconds.
[0037] According to some embodiments of the present application, the coating method in step S1 is using a spin coater to spin coat at a speed of 200 to 400 rpm / min for 30 to 90 seconds.
[0038] According to some embodiments of the present application, the coating method in step S2 is using a spin coater to spin coat at a speed of 800 to 1200 rpm / min for 30 to 90 seconds.
[0039] According to some embodiments of the present application, the horizontal tensile force is applied to the support layer, and the stretching is to 110% to 130% of the original horizontal length.
[0040] According to some embodiments of the present application, the ultrasonic treatment is ultrasonic treatment for 0.5-2 h using an ultrasonic cleaning machine.
[0041] In a third aspect, the present application provides a mechanoluminescence sensor, wherein the raw materials for preparing the sensor include the composite material for enhancing the mechanoluminescence response of the double-arch structure according to the first aspect of the present application.
[0042] In a fourth aspect, the present application provides an application of the composite material for enhancing the mechanoluminescence response of the double-arch structure according to the first aspect in the preparation of a sensor.
[0043] Compared with the existing mechanoluminescence materials, the present application has the following advantages:
[0044] 1) The mechanoluminescence material for enhancing the mechanoluminescence response of the present application is a mechanoluminescence material with an arch structure. The structure can overcome the limitations of ZnS:Cu luminescent materials in normal force sensing, and efficiently convert normal pressure into multi-directional tangential force coupling through a geometric mechanics conversion mechanism. When the normal load acts on the arch top, the arch surface produces a non-uniform strain distribution: the top region forms a compressive stress, while the arch foot region produces a tensile stress and a shear stress. Through this conversion mechanism, the sensing ability of ZnS:Cu luminescent materials to normal force is significantly improved.
[0045] 2) To further optimize the force-light conversion efficiency, a porous structure is introduced into the arch structure to obtain a mechanoluminescence material with a porous arch structure. Performance breakthrough is achieved through multi-stage deformation coupling and light field modulation. The porous structure forms local stress concentration at the hole edge, which improves the local strain of ZnS:Cu particles. At the same time, the secondary shear slip is generated by the buckling of the hole wall, which excites additional triboelectric effect. In addition, the porous structure reduces the average refractive index of the material, reduces the loss of total internal reflection, and can significantly improve the intensity of ML.
[0046] 3) The preparation process of the mechanoluminescence material with a porous arch structure provided by the present application is simple, has high preparation efficiency, is suitable for industrial production, and has good commercial value and application prospect.
[0047] Other features and advantages of the present application will be described in the following description, and some will become apparent from the description, or will be understood by those skilled in the art from the description. BRIEF DESCRIPTION OF DRAWINGS
[0048] The present application will be further described below in conjunction with the drawings and examples, wherein:
[0049] Figure 1 Response of ZnS:Cu mechanoluminescence material under different stresses;
[0050] Figure 2 The COMSOL software was used to simulate the stress conditions of the force-induced light-emitting material with different structures for Example 1 of the present application;
[0051] Figure 3 The schematic diagram of the formation principle of the three-dimensional arched ML material of Example 1 of the present application;
[0052] Figure 4 The schematic diagram of the preparation process of the porous arched ML sensor unit of Example 1 of the present application;
[0053] Figure 5 The test result graph of the regulation effect of adding different contents of SiO2 in PDMS on the elastic modulus and toughness of Example 1 of the present application;
[0054] Figure 6 The cross-sectional SEM graph of the porous arched ML sensor unit of Example 1 of the present application;
[0055] Figure 7 The optical test system independently built in the performance test of the present application;
[0056] Figure 8 The test result graph of the luminescence intensity of three structural ML sensor units under the same stress in the performance test of the present application. DETAILED DESCRIPTION
[0057] The concept and technical effects of the present application will be described below in conjunction with the embodiments to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, but not all the embodiments. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0058] The specific conditions not mentioned in the embodiments are carried out according to the conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments not mentioned by the manufacturer are conventional products that can be purchased on the market.
[0059] Example 1
[0060] The present embodiment provides a porous arched force-induced light-emitting material and a force-induced light-emitting sensor, and provides a preparation method thereof.
[0061] Theoretical simulation: first, the stress conditions of the planar thin film, the three-dimensional arched structure and the arched structure with porous structure under the same pressure were simulated by using the COMSOL software, and the simulation results are shown in Figure 2 , which verifies the effectiveness of the porous arched structure in enhancing stress concentration and optimizing luminescence performance.
[0062] Preparation process of the porous arched structure PL sensor:
[0063] 1) Preparation of the lower layer ink: mix PDMS, curing agent and SiO2 in a mass ratio of 10:1:0.6, stir in a vacuum stirring defoaming machine at a speed of 2500 r / min for 1 h to make them fully mixed and uniform to obtain the lower layer ink;
[0064] The curing agent is a curing agent in the Dow Corning SYLGARD 184 silicone rubber product. The curing agent can also use the curing agent commonly used in the art for PDMS curing, such as dibutyl phthalate (DBP);
[0065] 2) Preparation of the lower layer film: use a spin coater to spin coat the lower layer ink at a speed of 300 rpm / min for 60 s to uniformly coat the lower layer ink on a clean glass sheet substrate, and then place it in an electric heating constant temperature drying oven to cure at a high temperature of 80℃ for 2 h to form a stable lower layer film with a thickness of 143 μm;
[0066] 3) Stretching the lower layer film: apply a pre-stretch to the lower layer film, move and fix the cured lower layer film to a clamp, and pull it up to 120% of the original length in the horizontal direction;
[0067] 4) Preparation of the upper layer luminescent ink: mix PDMS, curing agent, NaCl and ZnS:Cu in a mass ratio of 10:1:20:10, stir in a vacuum stirring defoaming machine at a speed of 2500 r / min for 2 h to make them fully mixed and uniform to obtain the upper layer luminescent ink;
[0068] The NaCl is NaCl particles with a particle size range of 50-500 μm;
[0069] 5) Preparation of the upper layer film: use a spin coater to spin coat the upper layer luminescent ink at a speed of 1000 rpm / min for 60 s to uniformly coat the upper layer luminescent ink on the surface of the lower layer film in the stretched state, and cure it in an electric heating constant temperature drying oven at a high temperature of 80℃ for 2 h to make it fully crosslink and cure, with an upper layer film thickness of 476 μm; At this time, the double layer structure is fixed in the stretched state, and the NaCl particles are wrapped in the cured upper layer PDMS matrix to obtain a double layer film structure;
[0070] 6) Release stress to form an arched structure: carefully release the tensile strain applied to the lower layer film, and due to the residual stress generated by the difference in elastic modulus between the upper and lower layers, the structure will spontaneously bend to form a stable three-dimensional arched morphology ML material, and the formation process is shown in Figure 3 ;
[0071] 7) Dissolution pore-forming: the formed arch structure is immersed in hot water at 100°C, and ultrasonic treatment is performed for 1 h using an ultrasonic cleaner to accelerate the process of water dissolving NaCl particles and removing particle residues; after the dissolution is completed, uniform micron-sized holes are formed at the original positions of the NaCl particles, and a three-dimensional arch ML material with a porous structure is obtained;
[0072] 8) Post-processing: the porous arch structure ML material is taken out of the hot water and placed on a constant temperature table at 120°C for 2 h to dry to remove water; according to the application requirements, the porous arch structure ML sensor unit is finally obtained by cutting.
[0073] The preparation process of the porous arch structure ML sensor unit is as shown in Figure 4 .
[0074] In this embodiment, SiO2 is added to the lower layer ink to regulate its mechanical properties, especially to change the elastic modulus and toughness parameters of the lower layer film. In the previous exploration, 0wt%, 2wt%, 4wt%, 6wt%, 8wt% and 10wt% of SiO2 were added to the PDMS matrix respectively, and the stress-strain characteristics and elastic modulus and toughness values were tested, and the experimental results are shown in Figure 5 , wherein Figure 5 Figure a of which shows the stress-strain characteristics of SiO2 / PDMS composite materials with different doping ratios, and Figure b shows the elastic modulus and toughness values of SiO2 / PDMS composite materials with different doping ratios; the experimental results show that with the increase of SiO2 content, the elastic modulus of the PDMS composite material shows a continuous growth trend, indicating that SiO2 particles in the matrix can effectively improve the rigidity and anti-deformation ability of the material, but the toughness of the material shows a trend of first increasing and then decreasing. The initial stage of appropriate SiO2 doping can improve the energy absorption capacity of the PDMS matrix and improve its anti-fracture performance; but when the SiO2 content exceeds a certain threshold, the excessive filling of particles may lead to the accumulation of microstructure defects, causing the elongation at break of the material to decrease, thereby reducing its overall toughness. Combined with the above experimental results of SiO2 regulating the mechanical properties of PDMS composite materials, it is found that when the mass fraction of doped SiO2 is 6wt%, the material exhibits the best overall toughness characteristics, with high elastic modulus and good ductility, and is suitable for being used as a support layer to generate sufficient recovery stress during bending release, therefore, in Example 1, PDMS and SiO2 are mixed in a mass ratio of 10:0.6.
[0075] Comparative Example 1
[0076] This comparative example provides a planar film ML sensor, and the preparation process is as follows:
[0077] 1) Preparation of luminescent ink: PDMS, curing agent, NaCl and ZnS:Cu were mixed in a mass ratio of 10:1:20:10, and stirred in a vacuum stirring defoaming machine at a speed of 2500 r / min for 2 h to make them fully mixed and uniform to obtain the luminescent ink;
[0078] 2) The luminescent ink was spin-coated on a rectangular mold, and cured at 80°C in an electric heating constant temperature drying oven for 2 h to make it completely cross-linked and cured, forming a film with a thickness of about 476 μm;
[0079] 3) Demolding to obtain a planar film ML sensor unit.
[0080] Comparative Example 2
[0081] This comparative example provides an arch-shaped structure ML sensor, and the preparation process is as follows:
[0082] 1) Preparation of lower layer ink: PDMS, curing agent and SiO2 were mixed in a mass ratio of 10:1:0.6, and stirred in a vacuum stirring defoaming machine at a speed of 2500 r / min for 1 h to make them fully mixed and uniform to obtain the lower layer ink;
[0083] 2) Preparation of lower layer film: the lower layer ink was uniformly coated on a clean glass sheet substrate using a spin coater at a speed of 300 rpm / min for 60 s, and then placed in an electric heating constant temperature drying oven for curing at 80°C for 2 h to form a stable lower layer film with a thickness of 143 μm;
[0084] 3) Stretching the lower layer film: the pre-stretching was applied to the lower layer film, and the cured lower layer film was moved and fixed to the clamp, and pulled up to 120% of the original length in the horizontal direction;
[0085] 4) Preparation of upper layer luminescent ink: PDMS, curing agent, NaCl and ZnS:Cu were mixed in a mass ratio of 10:1:20:10, and stirred in a vacuum stirring defoaming machine at a speed of 2500 r / min for 2 h to make them fully mixed and uniform to obtain the upper layer luminescent ink;
[0086] 5) Preparation of upper layer film: the upper layer luminescent ink was uniformly coated on the surface of the lower layer film in the stretched state by a spin coater at a speed of 1000 rpm / min for 60 s, and cured at 80°C in an electric heating constant temperature drying oven for 2 h to make it completely cross-linked and cured, and the upper layer film had a thickness of 476 μm; at this time, the double layer structure was fixed in the stretched state to obtain a double layer film structure;
[0087] 6) releasing stress to form an arch structure: carefully release the tensile strain applied on the lower layer film, due to the difference in elastic modulus between the upper and lower layers, the structure will spontaneously bend and form a stable three-dimensional arch-shaped morphology ML material;
[0088] 7) post-processing: according to the application requirements, the final arch structure ML sensor unit is obtained by cutting.
[0089] Performance test:
[0090] 1. The cross-section of the porous arch structure ML sensor unit prepared in Example 1 was observed by electron scanning microscope, and the results are shown in Figure 6 It can be found that there are many pore structures in the ML material.
[0091] 2. The ML sensor units of Example 1, Comparative Example 1 and Comparative Example 2 were tested by mechanoluminescence. According to the optical signal acquisition requirements of the ML sensor, a complete optical test system platform was built, and the luminescence characteristics of the sensor under different stress conditions were analyzed. The optical test system mainly consists of a linear motor, a pressure sensor, a PCO scientific camera, a sample fixing device and a PC end data processing software, as shown in Figure 7 The linear motor as a loading device can apply controllable pressure and displacement to ensure accurate adjustment of external force during the test; the pressure sensor is responsible for real-time monitoring of mechanical parameters during the loading process, providing data support for quantitative analysis of optical signals and stress; the PCO scientific camera is used to record the instantaneous changes of the sensor under stress and light emission, and the pco.camware software is used for data acquisition and analysis.
[0092] The same normal force was applied to the ML sensor units of Example 1, Comparative Example 1 and Comparative Example 2, and their luminescence was recorded, as shown in Figure 8 It can be seen that under the same stress, the luminescence intensity of the porous arch structure ML sensor is nearly 10 times that of the planar film structure ML sensor, and the luminescence intensity of the arch structure ML sensor without porous structure is enhanced by about 1.7 times, which verifies the superiority of the porous arch structure in enhancing the normal force sensing ability of ZnS:Cu luminescent material.
[0093] The above embodiments of the present application are described in detail, but the present application is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A composite material that enhances the mechanoluminescent response of a double-layered dome structure, characterized by, The composite material is a double-layer arched structure composed of a support layer and a light-emitting layer; the preparation raw materials of the support layer include PDMS, a curing agent and SiO2; and the preparation raw materials of the light-emitting layer include PDMS, a curing agent and ZnS:Cu mechanoluminescence material.
2. The composite material of claim 1, wherein, In the preparation raw materials of the support layer, the mass ratio of PDMS, the curing agent and SiO2 ranges from 10:(0.5-2):(0.4-1).
3. The composite material of claim 1, wherein, In the preparation raw materials of the light-emitting layer, the mass ratio of PDMS, the curing agent and ZnS:Cu mechanoluminescence material ranges from 10:(0.5-2):(5-15).
4. The composite material of claim 3, wherein, The preparation raw materials of the light-emitting layer further include water-soluble particles, the particle size of the water-soluble particles ranges from 50 to 500 μm, and the mass ratio of the PDMS to the water-soluble particles ranges from 10:(10-30).
5. The method of producing a composite material according to any one of claims 1 to 4, wherein The method comprises the following steps: S1, mixing the preparation raw materials of the support layer, coating on a substrate, drying and curing to form the support layer, applying a horizontal tensile force to the support layer, and stretching to 105%-140% of the original horizontal length; S2, mixing the preparation raw materials of the light-emitting layer, coating on the support layer in the stretched state, drying and curing to form the light-emitting layer, and releasing the tensile force of the support layer to form a double-layer arched structure composite material.
6. The production method according to claim 5, wherein When the preparation raw materials of the light-emitting layer include water-soluble particles, the method further comprises the following steps: Placing the composite material obtained in step S2 in hot water, ultrasonic treatment, and dissolving the water-soluble particles to obtain a porous arched structure composite material.
7. The preparation method according to claim 5, characterized in that, The drying and curing method in steps S1 and S2 is heating and curing at 70-90 °C for 1-3 h.
8. The preparation method according to claim 5, characterized in that, The coating method in steps S1 and S2 is using a spin coater to spin coat at a speed of 200-1500 rpm / min for 30-90 s.
9. A mechanoluminescent sensor, comprising: The preparation raw materials of the mechanoluminescence sensor include the double-layer arched structure composite material for enhancing mechanoluminescence response according to any one of claims 1-4.
10. Application of the double-layer arched structure composite material for enhancing mechanoluminescence response according to any one of claims 1-4 in the preparation of a sensor.